An efficient semi-analytical simulation framework to analyse laminated prismatic thin-walled beams. (1st October 2018) - Wackerfuß, Jens; Kroker, Andreas M.
Highlights: Allows a highly systematic and efficient analysis of laminated thin-walled beams. Serve as a key ingredient to optimize cross-section geometry and stacking sequences. Method can easily and directly be embedded in existing optimization tools. Thus, long-winded and time consuming data transfers are avoided. Method based on predefined deformation modes used in up-to-date beam formulations. Abstract: An efficient semi-analytical simulation framework is presented, that allows a highly systematic analysis of the mechanical behaviour of laminated prismatic thin-walled beams. It is excellently suitable for extensive case studies and can serve as a key ingredient for the optimization of shape, geometry and stacking sequences of laminated beams. The proposed method can be coded as a stand-alone solution and easily and directly be embedded in existing numerical optimization tools, without the overhead of common simulation tools (like FE-codes). Thus, long-winded and time consuming data transfers are avoided. Additionally, as a consequence of the structural clearness of the proposed method, the simulation framework can also be used as an environment for the development and testing of new beam models. By analogy with existing models for thin-walled beams, the kinematic of the cross-section is described by a proper set of deformation modes. There are no restrictions regarding these modes, i.e. rigid body modes (axial extension, mayor- and minor-axis flexure, and torsion) as well as higher-order modes (involving warping, distortion and transverse bending of the cross-section walls) can be considered. It is shown that for each given set of modes, the resulting system of equations can be derived - both analytically and systematically - in a straight-forward manner. In contrast to common beam formulations, the introduction of both stress resultants and cross-section values is not required.